Assessment of seagrass beds and environmental conditions in Gili Noko, Gresik, East Java, Indonesia - Fatmala, Agustina; Pryono, Ach. Onky (UIN Sunan Ampel Surabaya, 2024)
Seagrass beds are critical coastal ecosystems with high biodiversity and significant contributions to nutrient cycling in surrounding waters due to their high productivity. This study focused on the seagrass ecosystem in the waters of Gili Noko, Gresik, East Java, Indonesia. Data collection was conducted using the quadrant transect method, measuring both physical and chemical water parameters, including temperature, clarity, substrate type, salinity, dissolved oxygen, and pH. The results identified two seagrass species, Enhalus acoroides and Thalassia hemprichii, in Gili Noko waters. The total seagrass density was recorded at 6.72 stands/m², while the percentage of seagrass cover was 6.09%, categorized as poor. The diversity index (H') was 0.89, indicating low diversity, whereas the uniformity index (E) was 0.45, and the dominance index (D) was 0.57, both categorized as moderate. Although the physical and chemical parameters of Gili Noko waters are within the optimal range for seagrass growth, the low density and cover highlight significant ecosystem degradation caused by anthropogenic activities and ecological pressures. Conservation efforts, including reducing human impacts and protecting natural habitats, are essential to restore the seagrass ecosystem. Further studies on rhizome growth rates and leaf turnover are recommended to better understand seagrass dynamics and support effective management strategies.